Eastern European Development and Public Policy
XV, 244 p.
Keywords: This book analyzes various important aspects of methodology and substance regarding economic, social, and political policy in East Europe directed toward achieving more effective, efficient, and equitable societal institutions. The chapters are authored by experts from within East Europe and also from East Europe research institutes elsewhere. The book combines practical policy significance with insightful causal and prescriptive generalizations. The emphasis is on the role of governmnetal decision-making and the important (but secondary) role of the marketplace, social groups, and engineering.